Measuring The Likelihood of Unregistered Marriage (The Perspective of Siyasah Jinayah) - Ubaidillah, Hasan (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
Unregistered marriage is not something uncommon in Indonesia, contrary to the promulgation of Law Number 1 of 1974 concerning Marriage requiring the state to only recognize the validity of a registered marriage. Unregistered marriage often puts women as victims and this practice tends to contravene Islamic law. There have been cases where women always end up with an unclear status as wives, considering that wives are not entitled to both juridical rights and Islamic law rights to cancel a marriage, while a divorce is not often clearly declared against wives by husbands. Despite the impacts resulting from unregistered marriage, this practice remains obvious in society. The notion demanding the criminalization of unregistered marriages is rising, while this view is opposed by some since it is deemed to contravene religious provisions. Departing from this polemic, this research employed a normative method to find out the legal standing of the criminalization of unregistered marriage pursuant to Islamic law. The research discovers that unregistered marriage is likely to take place according to the criminal perspective of Islam, especially when it is linked to merit and drawbacks in the matter. Although the legal standing of unregistered marriage is acceptable, overlooking the procedures set by the government is deemed to be disobedience since this instruction from the government as ulil amri is considered ta’zir citizens have to obey. Thus, criminalizing unregistered marriage is not taken as a proscription in terms of marriage, but it is implemented to respond to the disobedience of the governmental procedures.